Evaluation of the dry and wet weather recreational health risks in a semi-enclosed marine embayment in Southern California. (15th March 2017) - Lim, Keah-Ying; Shao, Stella; Peng, Jian; Grant, Stanley B.; Jiang, Sunny C.
Abstract: For many coastal regions around the world, recreational beach water quality is assessed using fecal indicator bacteria (FIB). However, the utility of FIB as indicators of recreational water illness (RWI) risk has been questioned, particularly in coastal settings with no obvious sources of human sewage. In this study we employed a source-apportionment quantitative microbial risk assessment (SA-QMRA) to assess RWI risk at a popular semi-enclosed recreational beach in Southern California (Baby Beach, City of Dana Point) with no obvious point sources of human sewage. Our SA-QMRA results suggest that, during dry weather, the median RWI risk at this beach is below the U.S. EPA recreational water quality criteria (RWQC) of 36 illness cases per 1000 bathers. During wet weather, the median RWI risk predicted by SA-QMRA depends on the assumed level of human waste associated with stormwater; the RWI risk is below the EPA RWQC illness risk benchmark 100% of the time provided that <2% of the FIB in stormwater are of human origin. However, these QMRA outcomes contrast strongly with the EPA RWQC for 30-day geometric mean of enterococci bacteria. Our results suggest that SA-QMRA is a useful framework for estimating robust RWI risk that takes into account local information about possible human and non-human sources of FIB. Graphical abstract: